Prevalence of asthma and allergies in 13–14-year-old adolescents from Luanda, Angola - Arrais, Margarete (2017)
SETTING: The few epidemiological studies on asthma and allergic diseases performed in Africa have shown that the prevalence of these diseases is high or increasing. No such studies have been performed in Angola. OBJECTIVE : To determine the prevalence of asthma and other allergic diseases in Angolan adolescents. DESIGN: This was a descriptive, observational, crosssectional study in the province of Luanda, Angola, using the International Study of Asthma and Allergies in Childhood study methodology in adolescents aged 13 and 14 years. Twenty-three (12%) public schools were randomly selected. Data were analysed using the Statistical Package for the Social Sciences version 22.0 software. RESULTS : A total of 3128 adolescents were included. The prevalence of asthma (wheezing in the previous 12 months) was 13.4%. The prevalence of rhinitis (sneezing, runny or blocked nose in the previous 12 months) was 27% and that of eczema (itchy skin lesions in the previous 12 months) was 20%; both were more prevalent in girls. Rhinitis was associated with a greater number of episodes of night cough in adolescents with asthma. Rhinitis and eczema, a split-type air conditioning system, and frequent intake (more than once per month) of paracetamol were associated with a higher risk of having asthma. CONCLUSION: Asthma and related allergic diseases are a public health problem in adolescents from Luanda. Preventive and control measures should be implemented.